The unexpected upside of depreciation: Bridging Europe's income divide - Alvaro Boitier; Livio Stracca (European Central Bank (ECB), 2025)
This paper investigates the impact of foreign exchange (FX) shocks on income inequality across 31 European countries from 2003 to 2021. Leveraging a unique database of household-level longitudinal data from the European Union Statistics on Income and Living Conditions (EU-SILC) and exchange rate data from the Bank of International Settlements, we investigate how currency devaluations and appreciations influence income distribution. Our findings indicate that a 1% currency devaluation decreases income inequality by 15 basis points within one year, while appreciations have the reverse effect. Contrary to previous studies focused on Latin America, which credit reductions in inequality to both labor mobility and union influence, our analysis identifies labor mobility as the primary factor in Europe. Furthermore, we discover that income changes are predominantly driven by variations in income per hour rather than hours worked.
Keywords: F31; F41; F44; 330; Foreign exchange; income inequality; labor mobility; EU-SILC; foreign currency; household income; social inequality; economic indicator; Europe; report